The Effect of Adolescent Boys' Attachment to Fathers on Social and Emotional Development - Zulfa, Vania; Mulyati, Mulyati; Ana, Nurhasana (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
Father involvement during adolescence remains relatively low and may negatively impact boys' social skills and emotional regulation. This research aims to provide deeper insight into how adolescent boys’ attachment to their fathers contributes to their social-emotional development. This study employed an associative quantitative method involving 71 respondents selected through purposive sampling, based on the criteria of male students aged 15–18 years who lived with their fathers. Data were collected using adapted research instruments, namely the Inventory of Parent and Peer Attachment (IPPA) and the Social-Emotional and Character Development Scale (SECDS). Simple linear regression analysis was used to test the hypothesis. The results show a significant influence of father–son attachment on social-emotional development (Fcount = 15.817 > Ftable = 3.98; p < 0.05). The determination coefficient (R Square) of 0.186 indicates that 18.6% of the variation in social-emotional development is explained by attachment to fathers, while the remaining 81.4% is influenced by other unexamined factors. The findings highlight the importance of fathers' involvement in fostering adolescents' social-emotional development. Therefore, schools are encouraged to optimize guidance and counseling services by providing family engagement programs, including parenting workshops and father–child counseling, to strengthen paternal support.